Grounds for repealing a resolution of a capital company - Szczepańska, Katarzyna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2018)
The paper presents the interpretation of grounds for repealing a resolution of a capital company (private and public limited) in the event of a conflict between such resolution and the company’s articles of association (statue), good practice, or when the intent of the resolution is contrary to the company’s interests or to the detriment of a shareholder,based on the views of representative legal doctrine and court rulings. These opinions are then confronted with views presented by legal theorists as well as the developments and changes of their interpretation in selected jurisdictions.